2001
DOI: 10.1038/35089098
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency induces the formation of an antenna ring around trimeric photosystem I in cyanobacteria

Abstract: Although iron is the fourth most abundant element in the Earth's crust, its concentration in the aquatic ecosystems-particularly the open oceans-is sufficiently low to limit photosynthetic activity and phytoplankton growth. Cyanobacteria, a major class of phytoplankton, respond to iron deficiency by expressing the 'iron-stress-induced' gene, isiA(ref. 3). The protein encoded by this gene has an amino-acid sequence that shows significant homology with one of the chlorophyll a-binding proteins (CP43) of photosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
316
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(330 citation statements)
references
References 22 publications
13
316
1
Order By: Relevance
“…This would imply the necessity for one or more additional chlorophyll bearing polypeptides on which the superfluous Chl molecules could be organised. One attractive hypothesis would be that Gloeobacter contains additional membraneintegral light-harvesting proteins resembling the LHC proteins found in chloroplasts or the recently found CP43 (Riethman and Sherman 1988;Park et al 1999) or IsiA (Boekema et al 2001;Bibby et al 2001) in cyanobacteria. Such a hypothesis would support the assumption that Gloeobacter is the predecessor of chloroplasts.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…This would imply the necessity for one or more additional chlorophyll bearing polypeptides on which the superfluous Chl molecules could be organised. One attractive hypothesis would be that Gloeobacter contains additional membraneintegral light-harvesting proteins resembling the LHC proteins found in chloroplasts or the recently found CP43 (Riethman and Sherman 1988;Park et al 1999) or IsiA (Boekema et al 2001;Bibby et al 2001) in cyanobacteria. Such a hypothesis would support the assumption that Gloeobacter is the predecessor of chloroplasts.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Furthermore, chloroplast PS I is associated with membrane integral light-harvesting complexes (LHC I), which were so far assumed to be absent in cyanobacteria. Only recently, PS I from Synechococcus and Synechocystis has been shown to associate with a membrane intrinsic antenna when grown under iron limitation (Boekema et al 2001;Bibby et al 2001). Because of their sequence homology to CP43 these polypeptides had been originally attributed to PS II (Riethman and Sherman 1988;Park et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of a chlorophyll binding protein, IsiA (Bibby et al, 2001;Boekema et al, 2001;Sandström et al, 2001), was first eliminated by showing normal fluorescence emission at 685 nm when 440-nm light was used for excitation. Similar 77K fluorescence peak at 685 nm in all the flv mutants and the wild type upon excitation of chlorophyll suggested that the unusual fluorescence pattern in the mutants is due to PBS.…”
Section: Flv2/flv4 Heterodimer and Sll0218 Protein Are Functionally Lmentioning
confidence: 99%
“…The spatial organization between LH1 and RC is still a matter of debate (1)(2)(3)(4)(5)(6)(7)(8), and no information on their assembly in a native system is available. Complementary to structure determination of individual components at near-atomic resolution (9-11), one of the main challenges today is to describe the supramolecular organization of the photosynthetic machinery in native membranes (12). From a more general standpoint, structural biology is in need of a technique with a lateral resolution and signalto-noise ratio good enough to identify individual components of a multiprotein complex in situ (13).…”
mentioning
confidence: 99%